2022
DOI: 10.51582/interconf.19-20.02.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

Ahmadov V.

Abstract: This paper evaluates the financial policy of oil-exporting Azerbaijan in the recent oil boom and bust period. Analysis of fiscal policy evaluates the fiscal sustainability and efficiency of government spending to upgrade domestic economy. Monetary policy evaluation measures the effect of the exchange rate policy on competitiveness of non-oil economy and capacity of Azerbaijan government to sustain macroeconomic stability in the oil-shock period. The share of the oil revenue in government budget increased signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…Notably, Azerbaijan's GDP per capita demonstrated a positive association with its imports from Pakistan, while exhibiting no statistically significant association with exports to Pakistan. Building upon prior research, one could argue that this phenomenon might be attributed to Azerbaijan's industrial lopsidedness (Hasanov, 2013;Ahmadov, 2022a). Despite its transformation into a prosperous economy, Azerbaijan continues to export primarily oil and gas, without high-value-added products that a significant market like Pakistan would import.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Azerbaijan's GDP per capita demonstrated a positive association with its imports from Pakistan, while exhibiting no statistically significant association with exports to Pakistan. Building upon prior research, one could argue that this phenomenon might be attributed to Azerbaijan's industrial lopsidedness (Hasanov, 2013;Ahmadov, 2022a). Despite its transformation into a prosperous economy, Azerbaijan continues to export primarily oil and gas, without high-value-added products that a significant market like Pakistan would import.…”
Section: Discussionmentioning
confidence: 99%
“…In essence, the ongoing trends in the onion sector underscore the critical importance of food security for small and developing nations, particularly in the midst of geopolitical tensions and the concurrent decline in cultivation and sown areas. The agricultural sector of Azerbaijan's economy is positioned as a key alternative to oil-led economic growth and development which creates challenges to diversify the economy (Ahmadov, 2022). Consequently, agricultural growth and development should be directed toward ensuring, at the very least, food security.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
“…The use of a mixed-methods approach in one recent study further demonstrated that specific non-oil industries in Azerbaijan, such as chlorine, soda, and sulfuric acid, have experienced de-industrialisation due to DD (Niftiyev, 2022). Various obstacles, such as exchange rate appreciation (Majidli, 2022), deficiencies in fiscal policy management of oil wealth (Ahmadov, 2022), and slow and ineffective industrial diversification (Guliyev, 2022), further confirm the undeniable presence of DD. In essence, recent studies underscore the crucial role of oil prices in shaping the Azerbaijani economy, influencing overall GDP, growth rates, and oil production (Sarkhanov, 2022).…”
Section: Dutch Disease In the Azerbaijani Economymentioning
confidence: 98%